Bid’ah Perspektif Fiqih Kontemporer - Rohim, Muhammad Yusuf Nur; M, Misbahuddin; Shuhufi, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Bid'ah is a concept that is often a topic of debate in the Muslim community. The word "bid'ah" comes from Arabic which means innovation or something new. In the context of the Islamic religion. bid'ah refers to any new practice or belief that has no basis in the teachings of the Koran and Sunnah. and is not supported by the consensus of scholars (ijma) or the analogy of Islamic law (qiyas). However. in its development. there have been different views among ulama about whether all forms of bid'ah are negative or there are certain forms that are acceptable and even bring benefits to Muslims. Bid'ah hasanah. or good heresy. is a term used to refer to innovations that do not conflict with the basic principles of Islam and bring benefits. This article aims to provide an in-depth understanding of the concept of heresy. its classification. as well as the views of ulama regarding this issue. Apart from that. this article will also discuss the impact of heresy in Islamic society and how people can avoid practices that are considered deviant heresy. With proper understanding. it is hoped that Muslims can maintain the purity of religious teachings and avoid divisions caused by differences in views regarding heresy.